2020
DOI: 10.5194/acp-20-11841-2020
|View full text |Cite
|
Sign up to set email alerts
|

Roll vortices induce new particle formation bursts in the planetary boundary layer

Abstract: Abstract. Recent studies have shown the importance of new particle formation (NPF) to global cloud condensation nuclei (CCN) production, as well as to air pollution in megacities. In addition to the necessary presence of low-volatility vapors that can form new aerosol particles, both numerical and observational studies have shown that the dynamics of the planetary boundary layer (BL) plays an important role in NPF. Evidence from field observations suggests that roll vortices might be favorable for inducing NPF… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
(59 reference statements)
0
11
0
Order By: Relevance
“…During the PEGASOS northern mission in spring 2013, a Cessna 172 airplane carrying scientific instrumentation was deployed to measure aerosol particles, trace gases and meteorological variables in the lower troposphere alongside the Zeppelin. The measurement setup and instrumentation on board have been described in previous studies (Lampilahti et al, 2020b;Schobesberger et al, 2013;Leino et al, 2019;Väänänen et al, 2016) Basic meteorological variables (temperature, pressure, relative humidity) were measured on board. Particle number size distribution was measured using a SMPS (10-400 nm size range, 2 min time resolution) and the number concentration of >3 nm particles was measured using an ultrafine condensation particle counter (UF-CPC, TSI model 3776) at 1 s time resolution.…”
Section: Cessna 172 Airplanementioning
confidence: 99%
See 2 more Smart Citations
“…During the PEGASOS northern mission in spring 2013, a Cessna 172 airplane carrying scientific instrumentation was deployed to measure aerosol particles, trace gases and meteorological variables in the lower troposphere alongside the Zeppelin. The measurement setup and instrumentation on board have been described in previous studies (Lampilahti et al, 2020b;Schobesberger et al, 2013;Leino et al, 2019;Väänänen et al, 2016) Basic meteorological variables (temperature, pressure, relative humidity) were measured on board. Particle number size distribution was measured using a SMPS (10-400 nm size range, 2 min time resolution) and the number concentration of >3 nm particles was measured using an ultrafine condensation particle counter (UF-CPC, TSI model 3776) at 1 s time resolution.…”
Section: Cessna 172 Airplanementioning
confidence: 99%
“…The 3-10 nm number concentration increased from less than 100 cm −3 to ∼ 400 cm −3 . Lampilahti et al (2021a) Figure 7. Vertical profile of 3-10 nm particle number concentration (black dots), temperature (blue line) and water vapor concentration (red line) measured on board the Cessna between 07:00-10:00 on 8 May 2013 in HTL.…”
Section: Vertical and Horizontal Distribution Of The Freshly Formed Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition a separate layer of sub-10 nm particles was observed above the ML in HTL. Lampilahti et al (2020b) showed that such layers in HTL are likely the result of NPF in the topmost part of the RL. Furthermore it was estimated that around 42% of the NPF events observed in HTL at the surface are entrained from such elevated layers.…”
Section: Discussionmentioning
confidence: 99%
“…The patchiness of nucleation mode particles can have other explanations such as vari-C5 able cloud cover (Wehner et al, 2007), land features (O'Dowd et al, 2009), and organized convection like roll vortices (Lampilahti et al, 2020).…”
mentioning
confidence: 99%